2014
DOI: 10.1186/1475-2875-13-462
|View full text |Cite
|
Sign up to set email alerts
|

PET-PCR method for the molecular detection of malaria parasites in a national malaria surveillance study in Haiti, 2011

Abstract: BackgroundRecently, a real-time PCR assay known as photo-induced electron transfer (PET)-PCR which relies on self-quenching primers for the detection of Plasmodium spp. and Plasmodium falciparum was described. PET-PCR assay was found to be robust, and easier to use when compared to currently available real-time PCR methods. The potential of PET-PCR for molecular detection of malaria parasites in a nationwide malaria community survey in Haiti was investigated.MethodsDNA from the dried blood spots was extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 19 publications
1
68
0
Order By: Relevance
“…For the area of low P. falciparum endemicity, a tracking results continuously (TRaC) survey was conducted in 2012 as part of Global Fund’s Round 8 activities that builds on the Strategic Plan against Malaria in Haiti. A 2011 nationwide survey reported Haiti to have a low national parasite prevalence of less than 1 % as estimated by PCR [ 16 ]. The 2012 survey was cross-sectional and implemented by Population Services International (PSI) utilizing a community-based household design in collaboration with Haiti’s Ministry of Health (MSPP) and the Centers for Disease Control and Prevention (CDC).…”
Section: Methodsmentioning
confidence: 99%
“…For the area of low P. falciparum endemicity, a tracking results continuously (TRaC) survey was conducted in 2012 as part of Global Fund’s Round 8 activities that builds on the Strategic Plan against Malaria in Haiti. A 2011 nationwide survey reported Haiti to have a low national parasite prevalence of less than 1 % as estimated by PCR [ 16 ]. The 2012 survey was cross-sectional and implemented by Population Services International (PSI) utilizing a community-based household design in collaboration with Haiti’s Ministry of Health (MSPP) and the Centers for Disease Control and Prevention (CDC).…”
Section: Methodsmentioning
confidence: 99%
“…Dried blood spots, on Whatman 903 protein saver cards, were analysed in duplicate by LNSP in June 2014 by polymerase chain reaction using photo-induced electron transfer fluorogenic genus-specific primers (PET-PCR). Sample preparation, storage, extraction, and assays were performed using protocols described previously [ 10 , 14 ], but modified to account for World Health Organization (WHO) Evidence Review Group recommendations made in March 2014 for PCR analysis in low transmission settings [ 15 ]. Briefly, the amplification of Plasmodium genus (5′–3′, forward primer: GCTCTTTCTTGATTTCTTGGATG; reverse primer: FAM-aggcgcatagcgcctgg AGCAGGTTAAGATCTCGTTCG) was performed in a 30 µL reaction containing 2X TaqMan Environmental buffer 2.0 (Applied BioSystems, Grand Island, NY, USA), 400 nm each of forward and reverse primers.…”
Section: Methodsmentioning
confidence: 99%
“…A community-based survey conducted in the Artibonite Valley during the rainy season of 2006 estimated a 3.1% prevalence of malaria by polymerase chain reaction (PCR) [ 9 ]. In 2011, a national community survey showed that, by all methods (microscopy, RDT and PCR), less than one percent of persons were parasitemic [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parasite genomic deoxyribonucleic acid (DNA), from lter paper and RDTs was extracted using QIAamp DNA Mini kit (Qiagen, QIAGEN, USA) according to the manufacturer's instructions. P. falciparum molecular identi cation was performed using the photo-induced electron transfer (PET)-PCR assay [33] on a Roche LightCycler 96 instrument (Roche Molecular Systems, Inc). Each experimental run included both a negative (no template) and a positive (3D7 P. falciparum strain) control.…”
Section: Multiplex Pcr Ampli Cation Of Pfmsp1 and Pfmsp2 Genesmentioning
confidence: 99%
“…Each experimental run included both a negative (no template) and a positive (3D7 P. falciparum strain) control. Samples with a cycle threshold (CT) of 40 or less were scored as positive [33][34]. The two Pfmsp1 and Pfmsp2 polymorphic genes were ampli ed by multiplex PCR.…”
Section: Multiplex Pcr Ampli Cation Of Pfmsp1 and Pfmsp2 Genesmentioning
confidence: 99%